Assessment of quality of life among chronic kidney disease patients undergoing hemodialysis in Sanglah General Hospital, Denpasar from April-May 2017 using EQ-5D-5L questionnaire - Ni Putu Rani Apsari Dewi; Yenny Kandarini; I Gde Ketut Sajinadiyasa; Triharnoto Triharnoto (Intisari Sains Medis, 2020)
Introduction: Hemodialysis or renal function replacement therapy is routine medical care for chronic kidney disease (CKD) patients. Many problems arise among patients with chronic kidney disease (CKD) undergoing hemodialysis, including physical, psychological, social and family relationships. Those will affect patient’s quality of life (QOL).Method: A cross-sectional study performed from April-May 2017 in Sanglah General Hospital Denpasar using EuroQol 5 (EQ-5D-5L) Questionnaire to assess the Health-Related Quality of Life (HRQOL). All of CKD patients undergoing hemodialysis in Sanglah General Hospital Denpasar that matched the inclusion and exclusion criteria were recruited to this study.Results: There were 46 patients participated in this study. Overall, 37 (86.05%) were male and divided into four age groups. The reported HRQOL as measured by means of EQ-5D-5L Index Value and EQ-VAS (Visual Analog Scale) Score was 0.71 ± 0.22 and 75.7 ± 0.635, respectively. The median of EQ-5D-5L Index Value and EQ-VAS Score was 0.71 [0.63-0.84] and 75 [70-80].Conclusion: This study provided associations between sociodemographic characteristics and their HRQOL. Healthcare providers should be aware of low HRQOL among patients with female gender, elderly patients and unemployed patients to improve their quality of life.